Effectiveness of Professional Teacher Education in Developing Educational Technology Skills in the Digital Era - Putranti, Adim Dwi; Rhamadani, Mega Wahyu; Sukmawarti, Sukmawarti; Utami, Asih (PT. Anagata Sembagi Education, 2025)
The transformation of digital technology has resulted in fundamental changes in various sectors of life, including the field of education which is experiencing a significant paradigm shift. This study aims to explore the effectiveness of teacher professional education in improving educational technology skills in the digital era. Along with the rapid development of technology, teachers' ability to integrate technology into the learning process becomes a key element in creating innovative and relevant learning experiences. This study uses a descriptive qualitative approach involving teachers who have participated in the professional education program as the main participants. Data were obtained through in-depth interviews, observations, and document analysis of the education programs followed by the teachers. The results show that professional education substantially improves teachers' skills in utilizing various technological tools, including learning software, digital platforms and technology-based teaching techniques. In addition, the program also encourages the development of positive attitudes towards the use of technology as an integral part of learning. However, the effectiveness of the program is inseparable from challenges such as limited access to technology facilities, lack of follow-up training, and differences in the level of individual readiness to adopt technology. This study concludes that systematically designed professional education with a focus on educational technology has great potential to strengthen teachers competencies in the digital era. These results provide important implications for policy makers and education providers to continue developing needs-based programs, providing adequate infrastructure, and creating a supportive ecosystem that supports the application of technology in learning.